'Til wrong feels right [Lyrics and more] - Iggy Pop Rockmusiker 1947- (Clarkson Potter/Publishers, 2019)
"Coinciding with the fiftieth anniversary of the first and eponymous The Stooges record, here for the first time are Iggy's collected lyrics, with stunning original photographs, illustrations and his and others' reflections on a genre-defining music career that spans five decades--the ultimate book for every rock and roll fan"--Penguin Random House website
"Lyrics and more" -- Cover
Originally published in hardcover in Great Britain by Viking, London, 2019
Keywords: Iggy Pop -- Rockmusiker -- 1947-; Lyrics -- Lyrik; Rock music / Texts; Pop, Iggy / 1947-; Pop, Iggy / 1947- / Portraits; Songs; Rock music; Rock lyrics; Portraits; Popular music lyrics; Musical texts; Song texts; Texts; Bildband